Positive Masculinity: Men’s Efforts to Eliminate Sexual Violence from the Home - Selvy Anggriani Syarif; Iin Mutmainnah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2024)
The socialization of positive masculinity perspectives among men is an effort to strengthen the positive aspects of masculinity in society. The goal is for men who embrace positive masculinity to promote equality and reduce genderbased violence. This research aims to describe the roles that men with a positive masculinity perspective can play within the family and how these roles can help reduce the potential for sexual violence. This study employs a literature review and content analysis, focusing on 10 positive values from the positive psychology/positive masculinity framework. The analysis was conducted on the Instagram accounts @bapak2id, @ id_ayahasi, @bumilpamil.id, @ayahbercerita.id, and @ lakilakibaru. The findings identify three key roles for men with a positive masculinity perspective: active involvement in parenting, participation in pregnancy and birth preparation, and fostering healthy family relationships. These roles align with Islamic teachings. The analysis of feeds, comments, and discussions (both offline and online) from these five accounts indicates strong support for the elimination of sexual violence in society.